2017
DOI: 10.1590/1678-457x.27816
|View full text |Cite
|
Sign up to set email alerts
|

Sonication enhances quality and antioxidant activity of blueberry juice

Abstract: Effect of sonication on the blueberry juice was studied by evaluating the pH, viscosity, electric conductivity, color, total sugars, soluble solids, polyphenol, anthocyanidin, and radical scavenging activities. There were not any remarkable (p > 0.05) change in pH and electric conductivity. However, viscosity and color of blueberry juice markedly (p < 0.05) enhanced with the extension of sonication time. Meanwhile, total sugars, soluble solids, polyphenol, and anthocyanidin were obviously enhanced (p < 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
9
30
2
Order By: Relevance
“…Namely, extended sonication (600 W, 28 kHz, 20°C, 30, 60, and 90 min) of grapefruit juice samples had increased antioxidant capacity, as determined with DPPH method. The same effect was recently noticed in treated blueberry juice samples, with parameters 0.5 Wcm ‐2 , 40 kHz, during 20, 40, and 60 min (Zou & Hou, ). The opposite findings from these studies implied that ultrasound treatment improves extraction of antioxidant compounds, and that is the main direct contribution to the higher nutritive value of the juices (Guerrouj, Sánchez‐Rubio, Taboada‐Rodríguez, Cava‐Roda, & Marín‐Iniesta, ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Namely, extended sonication (600 W, 28 kHz, 20°C, 30, 60, and 90 min) of grapefruit juice samples had increased antioxidant capacity, as determined with DPPH method. The same effect was recently noticed in treated blueberry juice samples, with parameters 0.5 Wcm ‐2 , 40 kHz, during 20, 40, and 60 min (Zou & Hou, ). The opposite findings from these studies implied that ultrasound treatment improves extraction of antioxidant compounds, and that is the main direct contribution to the higher nutritive value of the juices (Guerrouj, Sánchez‐Rubio, Taboada‐Rodríguez, Cava‐Roda, & Marín‐Iniesta, ).…”
Section: Resultssupporting
confidence: 81%
“…Namely, extended sonication (600 W, 28 kHz, 20°C, 30, 60, and 90 min) of grapefruit juice samples had increased antioxidant capacity, as determined with DPPH method. The same effect was recently noticed in treated blueberry juice samples, with parameters 0.5 Wcm -2 , 40 kHz, during 20, 40, and 60 min (Zou & Hou, 2017).…”
Section: The Effect Of Ultrasound On the In Vitro Antioxidant Capacsupporting
confidence: 83%
“…The increment of total soluble solids might be attributed to the increase in extraction efficiency with thermosonication treatment. This treatment damaged the cell walls and tissues of fruits and thus, more soluble solids can be found in the samples (Zou and Hou, 2017). In this study, the results of °Brix, pH, and acidity of sonicated apple juices were found to be different from previous studies (Abid et al, 2013;Gao and Rupasinghe, 2012).…”
Section: Resultscontrasting
confidence: 78%
“…Increase in the total phenolics, total flavonoids, and total flavanols may be due to increased extraction efficiency associated with the use of sonication. Numerous studies have illuminated that the generation of shock and shear waves along with mass transfer effects during the cavitation process in ultra‐sonication are responsible for elevated diffusion rates (Zafra‐Rojas et al, ; Zou & Hou, ). Moreover, this increment in total phenolics due to subjection of ultra‐sonication treatments might be explicated by the addition of hydroxyl radicals to aromatic structure present in phenolics (Bhat, Kamaruddin, Min‐Tze, & Karim, ).…”
Section: Resultsmentioning
confidence: 99%